Green Entreprenual Practices Among SMEs in Malaysia and Nigeria - Abdullahi Hassan Gorondutse; Maruf Gbadebo Salimon; Siti Noratisah Binti Mohd Nafi; Mohd Rashdan Bin Salehudden (International Journal of Supply Chain Management, 2020)
Entrepreneurial programs had paid great in assisting humanity. This action changes common man the way they live apart from generating careers. Despite the significant influence of entrepreneurship towards evolving a country’s economys growth these actions have its own weaknesses. Therefore, green entrepreneurs are trying to shape the behavior of doing business to emphasize the society’s new concerns on environmentalism and other ecological issues as they touch their business. Recently Green entrepreneurs are being seen important parts in the transition to green economies. World evidence indicates that people are increasingly becoming concerned about the environment and are gradually changing their behaviors accordingly. Since green entrepreneurial practices by SMEs in many countries were still in nascent stage it was recommended that relevant stakeholders should put in place measures meant to spur adoption and implementation by most entities including SMEs. Consequently, this research examines the state of green entrepreneurship and explores key factors that can towards helping green entrepreneurship specifically among SMEs in Malaysia and Nigeria by means of a quantitative method. Hence, it’s expected that the result of this study can pay meaningfully during policy design among government agencies answerable for environmental protection, this will encourage green entrepreneurship in Malaysia and Nigeria. The output of this research is significantly essential to the business owners as well as to the decision makers.